STRATEGI PENGEMBANGAN MUSEUM SRIBADUGA SEBAGAI OBJEK DAYA TARIK WISATA - Isni Soraya, - (2011)
The existence of an interest in the heritage objects that have led scientists in continental Europe hunt each other to search for these objects. This is based on perstise obtained by scientists from these historical objects. After the object is collected and then the scientists put it in a cabinet that is named Cabinet Of Curiousities (cabinet strange objects). After the display at the site, then the scientists showed the collection of strange objects to the general public that ultimately lead to public curiosity toward the origin of these objects are and how the process of making these historical objects. Finally in 1980 a scientist named Elias Asmole donate his collection to the University of Oxford for further study. This is an early milestone in the establishment of museums. Over time, the circulation of museums around the country are very significant in the region including Indonesia. There are so many museums built in Indonesia to protect endangered historical objects, as well as the museums built in the area of West Java, one of which is the museum Sri Baduga. At this time the museum Sri Baduga less enthused by the tourists to be able to serve as a choice tourist attractions in Bandung. This is based on several assumptions of society that the museum is a place containing objects that are very boring. This is exactly what led to the idea of research on the Development of museum objects and Sri Baduga as a tourist attraction. In this study, the method used is descriptive method by using the SWOT analysis tool to take the museum Sri Baduga as objects in this study. SWOT method is a method of research studies that try to describe the phenomenon or the relationship between the phenomena studied in a systematic, factual and accurate (Kusmayadi and Endar Sugiarto. 2000:29). From the research that has been done it is known that with the development of Sri Baduga museum can participate and support the Love Movement Museum (GNCM) 2010-2014 which was announced by the government. Movement of love museum, has been done since the beginning of 2010 until 2014 aimed to further increase knowledge and scientific community about heritage objects as well as to improve the existence of museums located in Indonesia because as we all know that the museum-contained Museum Indonesia has experienced significant growth from year to year.